TINJAUAN KEPENTINGAN PEMBANGUNAN MODAL INSAN DI MALAYSIA (Review on the Importance of Human Capital Development in Malaysia) - Hamat, Mohd Fauzi; Che Nordin, Mohd Khairul Naim (Journal of Al-Tamaddun, 2012)
Human capital development is one of the most popular terms in the discussion of development planning nowadays. It became significantly accepted and has been recognized as one of the cornerstone of economic development and progress of a country. Therefore, this article will discuss generally the concept of human capital development and its importance in development of the country at present and future. This discussion includes the concept of human capital in general, the importance of a balanced development of human capital based on Islamic development and the description of the needs of the development model in terms of the current national development.